PHARMACOKINETICS OF R- AND S-KETOPROFEN AFTER MULTIPLE INTRAVENOUS ADMINISTRATION OF KETOPROFEN RACEMATE IN CAMELS - AlKatheeri, N. A.; Wasfi, I. A.; Lambert, M. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text